Studying John : approaches to the fourth Gospel - Ashton, John, 1931- (Oxford ; New York : Clarendon Press, 1994)
Is historical criticism of the New Testament dead? In this telling collection of eight new studies on John's Gospel, John Ashton argues that this is very far from the case. Challenging the assumptions of methodologies which ignore the historical context in which the Gospel was composed, the author offers a spirited defence of historical criticism and provides practical demonstration of the many new insights which it has still to yield. The first two chapters treat in greater depth two key themes, the Prologue of John and the Jews, which appeared in the author's Understanding the Fourth Gospel. A third chapter is intended to supplement and correct this larger work. The rest of the book explores some of the serious theoretical weaknesses in much recent writing on the Gospel and makes some alternative proposals.
1. The Transformation of Wisdom -- 2. The Jews in John -- 3. Bridging Ambiguities -- 4. The Signs Source -- 5. The Shepherd -- 6. Narrative Criticism -- 7. The Discovery of Wisdom -- 8. Studying John.
Includes bibliographical references and index.
Keywords: Bible. -- Criticism, interpretation, etc